Unlocking the Dormant Potential of Wakalah bi al-Istitsmar: Addressing the Fixed-Return Market Gap and Mitigating Moral Hazard in Indonesian Islamic Deposit Contracts - Evan Ferdian Basri; Gemala Dewi; Rifki Ismal (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2025)
This research aims to address the absence of fixed-return instruments  in Indonesian Islamic banking, a gap that triggers the imposition of functions (functional displacement) on existing deposit-taking contracts (Mudharabah and/or wadi'ah) in order to satisfy risk-averse depositors. This structural condition is feared to trigger moral hazard practices that can distort the essence of the contract that leads to hilah ribawiyah, for example through the implementation of non-transparent profit smoothing management or the promise of fixed-return that is made unwritten. Using the juridical-normative method (doctrinal legal research), this study analyzes financial regulations (POJK and LPS Law) as well as DSN-MUI Fatwa No. 126/2019 and DSN Fatwa No. 152/2022 through a statutory and conceptual approach by adopting Archer's investment risk theory. The study found that  the Wakalah bi al-Istitsmar (WBI) Mutlaqah model with a performance incentive mechanism (Ujrah al-Ada') was proven to be able to create a stable return profile in a transparent manner. Furthermore, through the systematic interpretation of POJK No. 13/2021 and the application  of Archer's unrestricted risk framework  , the research proves that WBI Mutlaqah is functionally a liability with deposit characteristics, thus qualifying as an object of guarantee from the Deposit Insurance Corporation (LPS). The study concludes that the adoption of WBI Mutlaqah is a strategic need to mitigate displaced commercial risks, provide basic protection for risk-averse depositors, with the ultimate goal of maintaining the purity of risk-sharing characteristics  in the Mudharabah contract. The academic contribution of this study lies in enriching Islamic legal and financial scholarship through a doctrinal reconstruction of Wakalah bi al-Istitsmar as an alternative fixed-return deposit contract, as well as by strengthening the analytical linkage between investment risk theory, displaced commercial risk, and the deposit insurance regime within the Indonesian Islamic banking framework. The practical contribution of this study is the provision of an operational model and regulatory argumentation that may serve as a reference for regulators, Islamic banks, and Sharia Supervisory Boards in designing transparent, LPS-guaranteed fixed-return deposit products that are free from moral hazard practices